A Case of 'You Can Always Get What You Want'? Committee Assignments in the European Parliament. Issue 1 (19th March 2018) - Whitaker, Richard
Abstract: Committees are central to the operation of the European Parliament (EP), providing fora for the detailed consideration of legislative proposals. This article provides the first systematic assessment of how far and why Members of the European Parliament (MEPs) are successful in obtaining places on the committees to which they most want to be assigned. In doing so, we employ a new dataset of MEPs' committee preferences, information which has never before been systematically collected. Adapted forms of three theories of legislative organisation (distributive, informational and partisan) provide a framework for the analysis. The results indicate a high degree of success for MEPs in achieving the committee assignments they want, within the restrictions of proportional representation of party groups on committees. We find strong support for the informational approach to legislative organisation when examining variations in success rates. Nevertheless, there is also some evidence that partisan concerns influence the assignment process. This, in combination with the role of party coordinators in the EP, means that party groups and national parties in the EP attempt to limit the agency losses that might result from a high degree of self-selection in committee assignments.